(En)countering martial law rhythmanalysis, urban experience in Metro Manila, and Ilokano literature (1980-1984) - Galam, Roderick G. (2010)
Like many llokano writers, poet-fictionist Herman Garcia Tabin has never made his position on the Marcos dictatorship known. His works, which were written in the early 1980s and bound with the conditions produced by the regime, do not explicitly denounce Marcos's regime. However, they may be read as critiquing the social reality engendered by the dictatorship. Through a rhythmanalysis that implicates the constitutive role of the state and capital, this article examines depictions of life experiences of Metro Manila's impoverished people in Tabin's works. Tracing and following Tabin's moves and movements provide clues to that which he has neither publicly
avowed nor disavowed.
Keywords: Martial law; Martial law era; Dictatorship; Ilokano literature; Neoliberalism; Memory; Metro Manila